Analysis of New Order Government Policies and Their Implications for Islamic Education in the Republic of Indonesia - Yuliana, Evi; Yuliharti, Yuliharti; Hasyim, Hariza (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2026)
This study seeks to examine the educational policies of the New Order regime, particularly in Islamic religious education, and their impact on the advancement of Islamic education in Indonesia. The approach used is qualitative, using a library research method. Data sources are derived from secondary literature, including books, academic journals, and related scientific publications. Data were collected through a systematic search of documents analyzed descriptively and qualitatively through the following stages: source selection, theme categorization, content analysis, and conclusion drawing. The findings of this study indicate that the New Order's educational strategy prioritized the continuous and in-depth instillation of the ideals of Pancasila throughout society, primarily through education and training. The P4 improvement program and standardized curriculum facilitated the advancement of Islamic educational institutions, such as Islamic madrasas and universities, by integrating the national and religious curricula. This study concludes that the New Order era marked the beginning of the modernization and advancement of Islamic education within the national education system. This period saw a growing awareness of the challenges facing Islamic religious education, prompting the Ministry of Religious Affairs to formulate new policies that implemented various forms of Islamic education, including classical Indonesian Islamic boarding schools (pesantren), Islamic religious institutions (Diniyah), private Islamic schools, public Islamic elementary schools (SDIslamic elementary schools), and state Islamic religious institutions (LPIs). Consequently, the New Order period emerged as a significant chapter in the historical evolution of the modernization of Islamic education in Indonesia.